High preoperative bilirubin values protect against reperfusion injury after live donor liver transplantation. (23rd July 2015) - Spetzler, Vinzent N.; Goldaracena, Nicolas; Kaths, Johann M.; Marquez, Max; Selzner, Nazia; Cattral, Mark S.; Greig, Paul D.; Lilly, Les; McGilvray, Ian D.; Levy, Gary A.; Ghanekar, Anand; Renner, Eberhard L.; et al.
Summary Heme Oxygenase‐1 and its product biliverdin/bilirubin have been demonstrated to protect against ischemia/reperfusion injury (IRI). We investigated whether increased preoperative bilirubin values of transplant recipients decrease IRI. Preoperative bilirubin levels of live donor liver recipients were correlated to postoperative liver transaminase as a marker of IRI. Additionally, two recipient groups with pretransplant bilirubin levels >24 μmol/l (n = 348) and ≤24 μmol/l (n = 118) were compared. Post‐transplant liver function, complications, length of hospital stay, and patient and graft survival were assessed. Preoperative bilirubin levels were negatively correlated to the postoperative increase in transaminases suggesting a protective effect against IRI. The maximal rise of ALT after transplantation in high versus low bilirubin patients was 288 (−210–2457) U/l vs. 375 (−11–2102) U/l, P = 0.006. Bilirubin remained a significant determining factor in a multivariate linear regression analysis. The MELD score and its individual components as a marker of severity of chronic liver disease were significantly higher in the high versus low bilirubin group (P < 0.001). Despite this, overall complication rate (21.0% vs. 21.2%, P = 0.88), hospital stay [13 (4–260) vs. 14 (6–313) days, P = 0.93), and 1‐year graft survival (90.8% vs. 89.0%, P = 0.62) were similar in both groups. High bilirubin levels of liver recipients before live donor transplantation is associated with decreased postoperative IRI.